Lenkijos bibliotekų rankraštynų darbo bruožai - Skrodenis, Stasys (Knygotyra, 1974)
Almost in all the large libraries of Polish People’s Republic there are departments of manuscripts, in which treasures of culture of Poland and all over the world have been accumulated. The manuscripts belong to special collections which are worked up by their own principles and they fully answer the scientific purpose in the libraries. Polish libraries and the State Archives made an attempt in the type of manuscripts acquisition: all the material of state institutions and establishments have custody of records in the State Archives. The material of personal origin is kept in the libraries. There seems to be no precise limit and rather large deviation is possible particularly among ancient manuscripts. Archivists of the libraries pay great attention to processing,– making inventory and catalogues. All this speeds up the information and broadens it boundaries. Almost all the libraries publish scientific works. The microfilming of manuscripts is being done with heightened speed. The Station of Microfilms in Warsawa’s National library is ingaged in this work. Conservation and restoration of the unique material has been done on particularly scientific principles. The scientific principle has been emphasized by the work of the Laboratory of manuscripts conservation in the Central Archive of Ancient statements under the leadership of Dr Marina Husarska. Several scientific conferences on problems of restoration, conservation and preservation of paperware were held.